2018
DOI: 10.15537/smj.2018.7.22146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lipid abnormalities and cholesterol target value attainment in patients with stable coronary heart disease or an acute coronary syndrome in Saudi Arabia

Abstract: Objectives:To provide an overview of the extent of hyperlipidemia in very high-risk patients, and how lipid-lowering therapy (LLT) is used in a real-world setting.Methods:In this multicenter observational study, data were collected from LLT-treated patients with stable CHD or an ACS in Saudi Arabia between 2013 and 2014. Individuals were included if they were >18 years and had a full lipid profile available, recorded either prior to the baseline physician visit (CHD patients) or within 24-hours of admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It is well-established that ACS patients are at extremely high risk for cardiovascular incidents [10]. Also, dyslipidemia is a well-recognized risk factor for CHD progression, and this has been confirmed in many clinical studies [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well-established that ACS patients are at extremely high risk for cardiovascular incidents [10]. Also, dyslipidemia is a well-recognized risk factor for CHD progression, and this has been confirmed in many clinical studies [17].…”
Section: Discussionmentioning
confidence: 96%
“…Such risk can be diminished by good controlling of associated modifiable risk factors [9]. Lipid abnormality, for example, high concen-tration of triglycerides or Low-Density Lipoprotein (LDL) and low level of HDL, are famous for being highly widespread in ACS patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Where data were not available from the STARS-1 dataset, alternative sources were used, such as Al Sifri et al [ 21 ], a multicenter observational study investigating the prevalence of lipid abnormalities and cholesterol values in patients with stable dyslipidemia in the KSA. Baseline mean LDL-C levels were obtained from Altowaijri et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maximally tolerated statin (with or without ezetimibe) was chosen as the background LLT on top of which evolocumab may be administered as an adjunct therapy. Background LLT statin proportions applied in the model were sourced from Alburikan et al [ 52 ], and proportions of concomitant ezetimibe were sourced from Al Sifri et al [ 21 ]. For simplicity, we assumed that low-intensity statins reported were equal to moderate-intensity statins.…”
Section: Methodsmentioning
confidence: 99%
“…[ 14 15 16 17 18 ] Previous studies showed that less than one-third (28% women vs. 32% men) of the Arabian Gulf patients with ASCVD achieved their LDL-C targets. [ 16 19 20 21 ] However, little is known regarding the therapeutic management and achievement of guideline-recommended LDL-C goals in the UAE. The present study aimed to assess the real-world evidence of lipid-lowering therapy (LLT) utilization and achievement of LDL-C targets after ACS in the region of Abu Dhabi, UAE.…”
Section: Introductionmentioning
confidence: 99%